Dioxin-like compounds bioavailability and genotoxicity assessment in the Gulf of Follonica, Tuscany (Northern Tyrrhenian Sea). (January 2018) - Guidi, Patrizia; Corsolini, Simonetta; Bernardeschi, Margherita; Rocco, Lucia; Nigro, Marco; Baroni, Davide; Mottola, Filomena; Scarcelli, Vittoria; Santonastaso, Marianna; Falleni, Alessandra; Della Torre, Camilla; Corsi, Ilaria; et al.
Abstract: The Gulf of Follonica (Italy) is impacted by the chemical pollution from ancient mining activity and present industrial processes. This study was aimed to determine the bioavailability of dioxin-like compounds (DLCs) in coastal marine environment and to assess the genotoxic potential of waste waters entering the sea from an industrial canal. Moderately high levels of DCLs compounds (∑ PCDDs + PCDFs 2.18–29.00 pg/g dry wt) were detected in Mytilus galloprovincialis transplanted near the waste waters canal and their corresponding Toxic Equivalents (TEQs) calculated. In situ exposed mussels did not show any genotoxic effect (by Comet and Micronucleus assay). Otherwise, laboratory exposure to canal waters exhibited a reduced genomic template stability (by RAPD-PCR assay) but not DNA or chromosomal damage. Our data reveal the need to focus on the levels and distribution of DLCs in edible species from the study area considering their potential transfer to humans through the consumption of sea food. Highlights: DNA damage and micronuclei were found in transplanted mussels. Genomic stability was reduced after in vivo exposure to water from industrial canal. POPs and TEQs in the study area were higher than in the control sites. PCDFs/PCDDs ratio always > 1 and PCDFs contributed mostly to TEQs. Results support the hypothesis the nearby industrial site impacted the ecosystem.